-1(p+5)=-3(2p-10)

Simple and best practice solution for -1(p+5)=-3(2p-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1(p+5)=-3(2p-10) equation:


Simplifying
-1(p + 5) = -3(2p + -10)

Reorder the terms:
-1(5 + p) = -3(2p + -10)
(5 * -1 + p * -1) = -3(2p + -10)
(-5 + -1p) = -3(2p + -10)

Reorder the terms:
-5 + -1p = -3(-10 + 2p)
-5 + -1p = (-10 * -3 + 2p * -3)
-5 + -1p = (30 + -6p)

Solving
-5 + -1p = 30 + -6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '6p' to each side of the equation.
-5 + -1p + 6p = 30 + -6p + 6p

Combine like terms: -1p + 6p = 5p
-5 + 5p = 30 + -6p + 6p

Combine like terms: -6p + 6p = 0
-5 + 5p = 30 + 0
-5 + 5p = 30

Add '5' to each side of the equation.
-5 + 5 + 5p = 30 + 5

Combine like terms: -5 + 5 = 0
0 + 5p = 30 + 5
5p = 30 + 5

Combine like terms: 30 + 5 = 35
5p = 35

Divide each side by '5'.
p = 7

Simplifying
p = 7

See similar equations:

| 625=25x | | 0.5(4x+7)=0.6-(x-3) | | 4.3x+25.8=64.5-8.6x | | 21a=7 | | 1/3x+2+1/2x-3=90 | | V=567 | | 3(x-4)-12+2x-9= | | 4.84x=2x | | (-3x-4)-(-2x-1)=6 | | 4(3x-5)+6=x | | 5g+14g+3= | | 4m-2=5m+7 | | 30x^2-85x+60=0 | | -2(5+6k)+16=-90 | | A^3-7a^2+6a-10= | | 4a+11-1a=2 | | 6x-4+2x-2=90 | | 42=7f | | 1300.4624=2*3.14*38.44+2*3.14*6.2*h | | -3(-10+6x)=30 | | x+13+2x+17=180 | | 1300.46=2*3.14*38.44+2*3.14*6.2h | | 80=-16t^2+35t+12 | | 6x=40+x | | 1300.46=2*3.14*38.44+2*3.14*6.2 | | -6(3+2x)=-8-2x | | y=5x-3+5x+2 | | 5(7+2x)=x-13+5x | | 0.4(x+70)+0.2x=6 | | D^2-36d+324=0 | | s=10p | | 8(7-m)=-24 |

Equations solver categories